Advances in Chitosan Derivatives: Preparation, Properties and Applications in Pharmacy and Medicine - Dominika Žigrayová; Veronika Mikušová; Peter Mikuš (Gels)
Chitosan (CS) derivatives have been extensively investigated to enhance the physicochemical and biological properties of CS, such as its solubility, biocompatibility, and bioactivity, which are required in various areas of pharmacy and medicine. The present work emphasizes the ongoing research and development in this field, suggesting that the further exploration of CS derivatives could lead to innovative solutions that benefit society. The physicochemical properties, biological activities, methods of preparation, advantages, limitations, intended application areas, and realized practical implementations of particular CS derivatives are summarized and discussed herein. Despite the numerous promising attributes of CS derivatives as reported in this paper, however, challenges like target selectivity, standardization (purity, chitosan structural variability), and cost-effectiveness still need addressing for widespread implementation, especially in drug delivery. Therefore, basic research studies still prevail in CS drug delivery systems. However, for specific applications such as wound healing and tissue engineering, implementations of CS derivatives in practice are found to be more frequent. To obtain a more complex view of the topic, information from the scientific papers reviewed is supplemented with information from actual patents and clinical studies. Both basic research advances and the most successful and important medical implementations of CS derivatives are discussed concerning further challenges and future perspectives.